International Arbitration in Theory and Practice: Global Standards and the Case of Kosovo - Gojani, Skender; Jahmurataj, Isuf (Journal of Posthumanism, 2025)
International arbitration has become one of the most important mechanisms for resolving disputes in international trade and investment relations. This paper provides a detailed examination of the concept, functioning, and advantages of arbitration as an alternative to traditional courts. Through analysis of international legal sources such as the New York Convention and the UNCITRAL Model Law, as well as the rules of key institutions such as the ICC, LCIA, and ICSID, the paper elaborates on the forms, procedures, and practical impact of arbitration. It further explores the advantages and shortcomings of this method, as well as Kosovo’s position in this field. The methodology includes theoretical analysis, comparative approaches, and interpretation of international practices. This study aims to offer a comprehensive overview for students, professionals, and policymakers on the importance of arbitration in the international legal order.